2009
DOI: 10.1007/s00170-008-1893-7
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing AFM process productivity through improved fixturing

Abstract: Abrasive flow machining (AFM) is a nonconventional finishing process that deburrs and polishes by forcing an abrasive laden media across the workpiece surface. The process embraces a wide range of applications from critical aerospace and medical components to highproduction volumes of parts. One serious limitation of this process is its low productivity in terms of rate of improvement in surface roughness. Limited efforts have hitherto been directed towards enhancing the productivity of this process with regar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 19 publications
2
18
0
Order By: Relevance
“…It is also observed that the pressure decreases with increase in length of media flow travel. In AFM, it has been reported that enhancement in performance could be achieved by improved fixturing [27]. The machining parameters, such as concentration, mesh number and number of cycles were changed to determine their effects on the machining characteristics material removal (MR) and enhancement in surface finish in PEC Chandigarh [29].…”
Section: Iosr Journal Of Mechanical and Civil Engineering (Iosr-jmce)mentioning
confidence: 99%
“…It is also observed that the pressure decreases with increase in length of media flow travel. In AFM, it has been reported that enhancement in performance could be achieved by improved fixturing [27]. The machining parameters, such as concentration, mesh number and number of cycles were changed to determine their effects on the machining characteristics material removal (MR) and enhancement in surface finish in PEC Chandigarh [29].…”
Section: Iosr Journal Of Mechanical and Civil Engineering (Iosr-jmce)mentioning
confidence: 99%
“…A work-piece is a hollow cylindrical piece made up of yellow brass (65 % Cu, 35 % Zinc, 156 BHN hardness) and had been selected based on literature review [1,[5][6][7][8], past optimization of the developed basic AFM setup [26] and pilot experimentation [22,23] (refer to Fig. 3).…”
Section: Experimental Materialsmentioning
confidence: 99%
“…A fine finished part has better aesthetics, life, and functional performance due to its high polish, close dimensional controls and strength endurance. Finishing operations are labour intensive, least controllable and cost approximately 15 % of the total machining cost in the manufacture of precision parts [1]. The traditional finishing methods of grinding, lapping, honing and super finishing are good for the simple surface geometries but are found lacking in the fine finishing of intricate/hard surfaces.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Compared with the traditional machining method, the abrasive flow polishing technology can use the abrasive media flow to the complex structure of the hole and cavity deep hole polishing processing, but also according to the application requirements of parts, selecting different abrasive media to polish the parts, so as to obtain different polishing effect to meet the requirements of parts, abrasive flow processing principle shown in Fig. 1 [6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%